Proactive enteral tube feeding in pediatric patients undergoing chemotherapy. Issue 2 (9th September 2013) - Sacks, Nancy; Hwang, Wei‐Ting; Lange, Beverly J.; Tan, Kay‐See; Sandler, Eric S.; Rogers, Paul C.; Womer, Richard B.; Pietsch, John B.; Rheingold, Susan R.
Abstract Background To determine feasibility and safety of proactive enteral tube feeding (ETF) in pediatric oncology patients. Methods Pediatric patients with newly diagnosed brain tumors, myeloid leukemia or high‐risk solid tumors were eligible. Subjects agreeing to start ETF before cycle 2 chemotherapy were considered proactive participants (PPs). Those who declined could enroll as chart collection receiving nutritional standard of care. Nutritional status was assessed using standard anthropometric measurements. Episodes of infection and toxicity related to ETF were documented from diagnosis to end of therapy. A descriptive comparison between PPs and controls was conducted. Results One hundred four eligible patients were identified; 69 enrolled (20 PPs and 49 controls). At diagnosis, 17% of all subjects were underweight and 26% overweight. Barriers to enrollment included physician, subject and/or family refusal, and inability to initiate ETF prior to cycle 2 of chemotherapy. Toxicity of ETF was minimal, but higher percentage of subjects in the proactive group had episodes of infection than controls. Thirty‐nine percent of controls eventually started ETF and were twice as likely to receive parenteral nutrition. PPs experienced less weight loss at ETF initiation than controls receiving ETF and were the only group to demonstrate improved nutritional status at end of study. Conclusions Proactive ETF is feasible in children with cancer and results in improved nutritional status at end of therapy. Episodes of infection in this study are concerning; therefore, a larger randomized trial is required to further delineate infectious risks and toxicities that may be mitigated by improved nutritional status. Pediatr Blood Cancer 2014;61:281–285. © 2013 Wiley Periodicals, Inc.